Causal Reasoning About Human Behavior Genetics: Synthesis and Future Directions - Lynch, Kate E.; Morandini, James S.; Dar-Nimrod, Ilan; Griffiths, Paul E. (Behavior genetics, 2019)
When explaining the causes of human behavior, genes are often given a special status. They are thought to relate to an intrinsic human ‘essence’, and essentialist biases have been shown to skew the way in which causation is assessed. Causal reasoning in general is subject to other pre-existing biases, including beliefs about normativity and morality. In this synthesis we show how factors which influence causal reasoning can be mapped to a framework of genetic essentialism, which reveals both the shared and unique factors underpinning biases in causal reasoning and genetic essentialism. This comparison identifies overlooked areas of research which could provide fruitful investigation, such as whether normative assessments of behaviors influence the way that genetic causes are ascribed or endorsed. We also outline the importance of distinguishing reasoning processes regarding genetic causal influences on one’s self versus others, as different cognitive processes and biases are likely to be at play.